Synthesis, Characterisation and Biological Activity Screening Of Schiff Base Ligands Containing Isatin and Their Metal Complexes - Abdul Manan, Mohd Abdul Fatah (2008)
Six new Schiff bases formed from the condensation reaction of S-benzyldithiocarbazate (SBDTC) and S-methyldithiocarbazate (SMDTC) with selected diketones containing isatin derivatives namely isatin, 5-fluroisatin, 5-chloroisatin, 5-bromoisatin and methylisatin have been synthesised. Complexes of cobalt(II), nickel(II), copper(II), zinc(II) and cadmium(II) with these Schiff bases were prepared. These compounds were characterised by elemental analyses and various physico-chemical techniques. Single crystal X-ray analyses were carried out on five different compounds. X-ray crystallographic study of SB5ClISA and SB5BrISA Schiff bases proved that the condensation reaction between S-benzyldithiocarbazate with the isatin derivatives occur at the carbonyl position number 3 in the isatin ring. Crystal structure analyses of Co(II) and Ni(II) complexes showed that [Ni(SMISA)2]·MeCN and [Co(SMISA)2]·MeCN are six-coordinate and have a distorted octahedral structure with the ligands coordinated to the metal ions as uninegatively charged tridentate chelating agents via the azomethine nitrogen, thiolate sulphur atom and carbonylic oxygen atoms of the isatin moiety. Crystal structure of the Cu(SMISA)2 complex exhibited distorted square planar geometry with the ligands coordinated to the metal ion as uninegatively charged bidentate ions through the azomethine nitrogen and thiolate sulphur atoms. Unfortunately, none of the Zn(II) and Cd(II) complexes produced single crystals but, it is proposed, that they are also four-coordinated with a tetrahedral geometry. The Schiff bases and their metal complexes were evaluated for cytotoxic and antimicrobial activity. Cytotoxic screening was carried out against human breast cancer cells with positive estrogen receptor (MCF-7) and human breast cancer cells with negative estrogen receptor (MDA-MB-231). Some of the Schiff bases and metal complexes were found to be very active against these breast cancer cell lines with a CD50 values lower than Tamoxifen. Antimicrobial screening was carried out against four bacteria and three fungi. All compounds were found to have low or no activity against the selected bacteria and fungal strains.